Effect of nixtamalization of maize and heat treatment of soybean on the nutrient, antinutrient, and mycotoxin levels of maize-soybean-based composite flour - Matendo, Rehema Esther; Imathiu, Samuel; Udomkun, Patchimaporn; Owino, Willis O. (Frontiers in Sustainable Food Systems, 2023)
Poor energy and nutrient-dense complementary food for infants have resulted in malnutrition and poor growth. Some processes are known to improve the nutritional value while reducing the antinutrient factors in food formulations. Maize-soybean-based composite flours from nixtamalized maize and heat-treated soybean were used to formulate six composite flours (CFs). The proximate composition, mineral content, antinutritional effect, mineral molar ratios, and mycotoxin level were investigated. The nixtamalization of maize and the heat treatment of soybean substantially improved the nutritional properties of the CFs. The pH value varied with the nixtamalization process, from 6.82 ± 0.7 to 9.32 ± 0.4. The energy content of the complementary foods was in the range of 354.77 ± 3.2 to 429.56 ± 4 kcal, meeting the minimum standard set for a cereal-based CF, which is 400 kcal. The protein values of the CFs (9.48 ± 0.3 to 13.92 ± 1.92%) on a dry weight basis were slightly below 15% of the recommended levels set by Codex. The antinutrient levels were reduced with nixtamalization and heat treatment. The molar ratio of phytate to minerals (calcium, zinc, and magnesium) was lower than the reported critical value, except for phytate to iron, where only whole maize, nixtamalized maize, and composite flour 3 (CF3) had a molar ratio that exceeded the reported critical value of 1. Although all composite flours were contaminated with mycotoxin, aflatoxin content in CFs ranged from 1.35 ± 0.67 to 13.8 ± 0.29 g/kg and from 0.3 ± 0.07 to 0.63 ± 0.015 mg/kg for fumonisin. Only the control and CFs made from the untreated maize did not meet the EU regulatory threshold (4.0 g/kg) for total aflatoxins and total fumonisin (4 mg/kg). The soybeans were not contaminated with the mycotoxins. The composite flour 5 (Composite flour 25% HS + 75% NixM) can be considered the best composite flour with regard to its nutritional properties, mineral, antinutrient, and mycotoxin content. These findings have shown that nixtamalization and heat treatment can improve the nutritional properties and food safety of composite flours.